A frissdiplomások végzéskori elvárásainak és három éves munkaerőpiaci tapasztalatainak összehasonlítása - Tamándl, László (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
The higher educational institutions in the USA and some countries of Europe have already examined the careers of their alumni for more decades. This process has many positive signs: it makes the connections between the institutions and the alumni stronger, just like between the institutions and the labour market; in addition it attracts attention to the building and the possible changes. In Hungary the inauguration of the compulsory career-following-system was laid down in the Law of Higher Education in 2005 (2005/CXXXIX. act of the higher education). The career-following is very important for the Széchenyi István University, so is the utilization of its results. The inauguration of the career-following-system of the alumni (the Hungarian abbreviation, that will be used henceforth: DPR) in the higher education is voluntary. As far as the representativity is concerned, the universities and colleges have unfortunately problems in Hungary how to achieve their alumni and how to get them to cooperate. A successful institutional DPR needs live connections with the students over their study and after it as well.